Mixed Ligand-metal Complexes of 2-(butan-2-ylidene) Hydrazinecarbothioamide- Synthesis, Characterization, Computer-Aided Drug Character Evaluation and in vitro Biological Activity Assessment - Khan, Tahmeena; Ahmad, Rumana; Azad, Iqbal; Raza, Saman; Joshi, Seema; Khan, Abdul R. (Current Computer - Aided Drug Design, 2021)
Background: Mixed ligand-metal complexes are efficient chelating agents because of their flexible donor ability. Mixed ligand complexes containing hetero atoms sulphur, nitrogen and oxygen have been probed for their biological significance. Methods: Nine mixed ligand-metal complexes of 2-(butan-2-ylidene) hydrazinecarbothioamide (2- butanone thiosemicarbazone) with pyridine, bipyridine and 2-picoline as co-ligands were synthesized with Cu, Co and Zn salts. The complexes were tested against MDA-MB231 (MDA) and A549 cell lines. Antibacterial activity was tested against Staphylococcus aureus and Escherichia coli. The drug character of the complexes was evaluated on parameters viz. physicochemical properties, bioactivity scores, toxicity assessment and Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) profile using various automated softwares. Molecular docking was performed against Ribonucleotide Reductase (RR) and topoisomerase II (topo II). Results: The mixed ligand-metal complexes were synthesized by condensation reaction for 4-5 h. The characterization was done by elemental analysis, 1H-NMR, FT-IR, molar conductance and UV spectroscopic techniques. Molecular docking results showed that [Cu(C5H11N3S)(py)2(CH3COO)2], [Zn(C5H11N3S)(bpy)(SO4)] and [Zn(C5H11N3S)(2-pic)2(SO4)] displayed the lowest binding energies with respect to RR. Against topo II [Cu(C5H11N3S)(py)2(CH3COO)2], [Cu(C5H11N3S)(bpy)(CH3COO)2] and [Zn(C5H11N3S)(2-pic)2(SO4)] had the lowest energies. The druglikness assessment was done using Leadlikeness and Lipinski’s rules. Not more than two violations were obtained in case of each filtering rule showing drug-like character of the mixed ligand complexes. Some of the complexes exhibited positive bioactivity scores and almost all the complexes were predicted to be safe with no hazardous effects as predicted by the toxicity assessment. Ames test predicted the non-mutagenic nature of the complexes. Conclusion: In vitro activity evaluation showed that [Zn(C5H11N3S)(py)2(SO4)], [Co(C5H11N3S(bpy) (Cl)2] and [Cu(C5H11N3S)(2-pic)2(CH3COO)2] were active against MDA. Against A549 [Co(C5H11N3S)(py)2(Cl)2], [Cu(C5H11N3S)(py)2(CH3COO)2] and [Co(C5H11N3S(bpy)(Cl)2] were active. Antibacterial evaluation showed that [Co(C5H11N3S)(bpy)(Cl)2], [Zn(C5H11N3S)(2-pic)2(SO4)] and [Cu(C5H11N3S)(2-pic)2(CH3COO)2] were active against S. aureus. Against E. coli, [Zn(C5H11N3S)(2- pic)2(SO4)] showed activity at 18-20 mg dose range.
Keywords: druglikeness